KH ABDURAHMAN WAHID (1940-2009) DAN DAKWAHNYA DI INDONESIA - Putra, Robby Aditya; Akhyar, Ramadiva Muhammad (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 16 No 1 (2020)DO - 10.24239/al-mishbah.Vol16.Iss1.188, 2020)
Gus Dur's pluralism is closer to social pluralism, but also leads to humanism (respecting the lives of others). Pluralism of this kind emphasizes on building a nation that is unified over the differences. This kind of da'wah pathway can only be realized if Da'wah is not merely understood as a conventional activity. Da'wah should be brought to the wider realm, the political path. Preaching activists moved to the teachings of Islam so that Islam can be made an ideology of the country, or at least every government or state policy always with Islamic values so that Islamic teachings are based on the nation's political life.